THE EFFECT OF TECHNOLOGICAL BEHAVIOR TOWARDS THE ADOPTION OF EDUCATION INTEGRATED SYSTEM AMONG NEW INTAKE STUDENTS - Ayub Ilfandy Imran (Lingkar Studi Komunikasi (LISKI), 2019)
The implementation of technological system on the members of organization has always create great opportunities as well as intense challenges. On educational settings, the introduction of integrated technology system on the newly intake students provides the possibility of both acceptance and resistance. The enforcement of Telkom University’s Integrated Academic Information System (iGracias) on its institutional members has create great challenges to achieve its adoption, especially among its new members. Specifically, this study aims at measuring the level of awareness, perception, and attitude towards iGracias and its impact on the students’ actual adoption. Designed with a quantitative approach, this research seeks to test the formulated hypotheses and to validate a new model based on the responses from 200 newly intake students of 2018 academic year at Telkom University. The results of the study indicate that students’ awareness and perception are positively and significantly related to their attitude towards the iGracias. the analysis also point out a positive and significant relationship between attitude on iGracias towards its adoption. Furthermore, the results found that the attitude towards the iGracias has mediating effects on both awareness and perception on the technology. Finally, the study also manages to validate a new model and argues its practical relevance on the similar organizational context.